1999
DOI: 10.2165/00007256-199928060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Strength and Endurance Training

Abstract: Concurrent strength and endurance training appears to inhibit strength development when compared with strength training alone. Our understanding of the nature of this inhibition and the mechanisms responsible for it is limited at present. This is due to the difficulties associated with comparing results of studies which differ markedly in a number of design factors, including the mode, frequency, duration and intensity of training, training history of participants, scheduling of training sessions and dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
3
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(124 citation statements)
references
References 62 publications
3
115
3
3
Order By: Relevance
“…strength training objective at P1) and maximal aerobic power (i.e. endurance training objective at P2), because these are thought to be two modes of training that lead to opposite physiological adaptations at the peripheral level that prevent the body from optimally and simultaneously adapting to both of them (Leveritt et al 1999). Thus, while hypertrophy training would be attempting to increase contractile protein synthesis in the muscle, causing considerable metabolic and hormonal stress at the cellular level, training for aerobic power would require the muscle to increase its oxidative capacity (Docherty and Sporer 2000;Sale et al 1990a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…strength training objective at P1) and maximal aerobic power (i.e. endurance training objective at P2), because these are thought to be two modes of training that lead to opposite physiological adaptations at the peripheral level that prevent the body from optimally and simultaneously adapting to both of them (Leveritt et al 1999). Thus, while hypertrophy training would be attempting to increase contractile protein synthesis in the muscle, causing considerable metabolic and hormonal stress at the cellular level, training for aerobic power would require the muscle to increase its oxidative capacity (Docherty and Sporer 2000;Sale et al 1990a).…”
Section: Discussionmentioning
confidence: 99%
“…One important aspect was controlling for training volume and, especially, limiting the frequency of resistance training to only three sessions per week because, as already addressed in the introduction, higher frequencies have proved to compromise strength gains in most concurrent training studies. Research has also highlighted the importance of the order and timing of the aerobic and strength training sessions in order to minimize possible interference effects (Leveritt et al 1999(Leveritt et al , 2000Sale et al 1990b;Sporer and Wenger 2003). Thus, insufficient recovery between training sessions might limit simultaneous adaptations to strength and endurance training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robert C. Hickson (1980) was the first author to describe this procedure and a number of investigations into the effects of this form of training have since been conducted. Reviews of the literature carried out by Leveritt, Abernethy, Barry, and Logan (1999), and Paulo, Souza, Laurentino, Ugrinowitsch, and Tricoli (2005) reported that some authors state that the combination of the two training methods in a single session may have a considerable structural and metabolic impact on muscle fibers, resulting in the loss of contractile force and physical capacity (Hickson, 1980). According to Baar (2006), however, little was known in the 1980s regarding the effects concurrent training on physical fitness, the increase in muscle mass and mitochondrial density.…”
Section: Introductionmentioning
confidence: 99%